Needs analysis of professionalism in tourism education: Students’ perceptions in vocational higher education - Wardani, Peni Arianita; Farhan, Muhamad; Indrastana, Nodistya Septian; Rahmanita, Meiga; Rachman, Nur Afni; Andadari, Mutika (P3M Politeknik Negeri Jember, 2024)
Professionalism is a cornerstone of success in the tourism industry, underscoring the need for targeted skill development among students pursuing tourism-related education. Recognising this, Politeknik Negeri Jember (Polije) launched the Edu tourism teaching factory. This innovative initiative integrates Tourism Destination Study Program students into real-world industry environments, fostering professionalism through experiential learning. This effort aligns with Polije’s outcome-based education framework, emphasising the production of industry-ready graduates. A critical component of this initiative is the development of structured teaching materials that address the specific aspects of professionalism required in the tourism sector. However, identifying these components necessitates comprehensive research into students’ perceptions and industry needs. Grounded in the context of global tourism, where professionalism directly impacts service quality and customer satisfaction, this qualitative study explores the requirements for teaching materials that promote professionalism. Using simple random sampling, 125 students were surveyed, complemented by interviews with program managers, Edu tourism administrators, and student representatives. The Miles and Huberman technique was employed for data analysis, integrating triangulated survey and interview data. Key findings revealed that students prioritise politeness, communication skills, and respect, followed by attention to detail, helpfulness, and consideration. Preferred teaching tools include bilingual video tutorials on service excellence, reflecting the industry’s global nature. This study has significant implications for global tourism education and practice. It addresses the critical need to standardise professionalism training. By aligning teaching materials with real-world industry demands, this research supports enhancing service standards and fostering a globally competitive tourism workforce.